KEPEMIMPINAN TRANSFORMASIONAL PAUD - Salwa Dinata, Azahra; Khoirunnisa Fajrani, Fadya; Faizatulkhayah; Wella Andina, Riziq; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This conceptual article examines the importance and implementation of transformational leadership in improving the management quality of Early Childhood Education (PAUD) institutions. The aim is to explain how a change-focused leadership style can inspire and motivate educators to function optimally in facing today's educational challenges. The discussion covers four key aspects of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized attention, as well as the integration of leadership values from a Qur'anic perspective that prioritize kindness, honesty, and responsibility. Through a literature review, this article concludes that the role of the principal as an agent of transformation, a driving force, and a pioneer is crucial in creating a supportive work environment, enhancing teacher morale, and stimulating learning innovation in the digital age. It is hoped that the implementation of this leadership model will significantly contribute to the quality of educational services for children during their development.